Case reportSuccessful closure of a very large secundum atrial septal defect with the Occlutech Figulla® device - Tasal, Abdurrahman; Bacaksiz, Ahmet; Erdogan, Ercan; Sonmez, Osman (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
Atrial septal defect (ASD) is one of the most common adult congenital heart diseases. It is characterized by a defect in the interatrial septum allowing pulmonary venous return from the left atrium to pass directly to the right atrium. It can result in pulmonary hypertension, congestive heart failure and cerebrovascular accident, so elective closure is recommended for all ASDs with evidence of right ventricular overload or with a clinically significant left-to-right shunt. Treatment methods include surgical and percutaneous closure. Transcatheter device closure is the method of choice in most centres nowadays. The rate of complications and length of hospital stay are lower compared to surgical closure. This technique can be performed successfully for a wide range of defects. Very large defects with inadequate rims could decrease the procedural success. The Occlutech Figulla ASD Flex Occluder is a new percutaneous closure device with some advantages such as higher flexibility, minimized amount of material implanted, and absence of the left atrial clamp in order to reduce trauma risk and clot formation on the left atrial disc. We think that these unique features could increase the procedural success rate. We report a patient with a very large defect who underwent transcatheter device closure using the Occlutech Figulla ® device.